Children with Febrile Seizures have Lower Zinc Levels - SyedaMamoonaQudrat,NajafMasood,AmmaraKhalid,TanzeelaRani,MobeenTabussum,RaiMohammadAsghar, SyedaMamoonaQudrat,NajafMasood,AmmaraKhalid,TanzeelaRani,MobeenTabussum,RaiMohammadAsghar (Journal of Rawalpindi Medical College, 2020)
Objective: To find the association between zinc deficiency and febrile seizures in children of 6 months and 5 years of age. Materials and Methods: Cross-Sectional Descriptive Study was carried out at the Department of Pediatrics, Benazir Bhutto Hospital, Rawalpindi for a duration of six months (From 11th March to 31st August 2017). After taking approval of the Ethical Research Committee of Rawalpindi Medical College and taking informed consent from the parents/ guardians, children selected according to the inclusion/exclusion criteria. Patient profile including name, age, sex, address, hospital number, serial number, date of inclusion in the study was noted. Data was collected from the Patient’s charts and/or by direct interview of the child’s guardian. Using aseptic measures, 2ml of blood from venipuncture utilizing a 22-gauge antiseptic needle, in no more than 24 hours of hospital visitation was reserved. Evaluation of serum zinc was completed in no more than 6 hours of collection. The copy was then given to the lab testing and thus this report was then approved by the physician. Results: In our study, out of 145 cases, 52.41%(n=76) were between 1-3 years of age whereas 47.59% (n=69) were between 4-6 years of age, the mean and standard deviation was calculated as 3.54 + 1.50 years, 50.34% (n=73) were male whereas 49.66% (n=72) were females. Mean serum zinc levels were calculated as 64.28 + 12.13 mcg/dl. The frequency of hypozincemia in febrile seizures among children presenting at tertiary care hospitals was 54.48% (n=79). Conclusion: These analysis outcomes depicted that children with febrile seizures had notably lesser serum zinc measures.